Grading of supratentorial gliomas using MR diffusion tensor imaging - Sing, Tan Kia (2016)
Background and Purpose: Gliomas, being the most common primary brain tumours are usually located at the supratentorial regions in adults. They are classified into low grade (grade I and II) and high grade (grade III and IV) based on WHO classification. Conventional MR imaging is essential to characterise the tumour morphology but lack accuracy in determining the grade of tumours. Advanced MRI technique such as DTI has emerged over the past decades as an additional method to further evaluate the brain tumours at the microstructural and physiological levels. Accurate grading of gliomas is important to determine the mode of treatment and sequences of management for patients. Therefore, this study aims at retrospectively determines whether FA or ADC values at 3-Tesla MR DTI are significantly different between low grade and high grade supratentorial gliomas. FA and ADC values between the gliomas and normal cerebral hemisphere are also being compared. Methodology: Sixteen patients aged 18 years old and above with newly diagnosed supratentorial gliomas with histopathological results were included. Their MRI with DTI sequence were retrieved from PACS into extended MR workspace for data analysis. DTI data was co-registered with post-gadolinium T1 weighted images. Four ROIs were drawn at the anterior, posterior, lateral and medial margins of tumours. ROIs were also placed at the contralateral NAWM of the opposite lobe. Comparison of FA and ADC values between low grade and high grade gliomas, and between gliomas with contralateral NAWM was performed using Mann-Whitney U test and Wilcoxon signed ranks test respectively. Results: There was significant difference between FA of low grade and high gliomas, and between FA and ADC of gliomas and contralateral NAWM (p < 0.05). No statistical significant difference was found between the ADC of low grade and high grade gliomas (p = 0.129). Conclusion: FA values generated from DTI can be used to grade gliomas. ADC values of low grade gliomas are higher than that of high grade gliomas but are not statistical significantly different.